SENTINEL LYMPH NODE CONCEPT IN DIFFERENTIATED THYROID CANCER - Markovic Ivan; Dzodic Radan (Sanamed, 2014)
Introduction: Differentiated thyroid carcinoma (DTC) account up to 90% of all thyroid malignacies, and represents the most common malignant tumors of endocrine system. The incidence of papillary thyroid carcinoma (PTC), especially small tumors is rapidly increasing during past three decades. At the time of diagnosis, the incidence of lymph node metastases (LNM) ranges from 80 to 90%. During the last 15 years, LNM were recognized as bad prognostic factor for both local-regional relapse (LRR) and cancer specific survival. There is general agreement that neck dissections are indicated in cases of clinically apparent LNM. The subject of the current controversy is the surgical treatment of occult LNM that remain unrecognized on preoperative diagnosis (cN0). The extent of operations of the lymph nodes ranges from “wait and see” so-called “Western school” principle substantiated the role of applying ablative I131therapy and frequency peroperative complications (recurrent laryngeal nerve injury and hypoparathyroidism), especially for less experienced teams to mutual prophylactic dissection of the central and lateral compartments so-called “Japanese school” due to the limited use of radioactive iodine therapy and significantly lower operating morbidity if dissetion was done during primary operation. Despite high prevalence of occult LNM, existing controversies regarding diagnosis, longterm prognostic impact and extent of lymph node surgery, motivated some authors to apply consept of sentinel lymph node biopsy (SLNb) in DTC, taking into account excellent results of SLN concept in breast cancer and skin melanoma. This review presents the summarized results of relevant studies and three meta-analysis of accuracy and applicability of SLN concept in patients with differentiated thyroid carcinoma.